The Effect of Branched‐Chain Fatty Acid Alkyl Esters on the Cold‐Flow Properties of Biodiesel. (10th June 2019) - Dunn, Robert O.; Wyatt, Victor T.; Wagner, Karen; Ngo, Helen; Hums, Megan E.
Abstract: Biodiesel (fatty acid methyl esters [FAME]) is produced from various fats, oils, and greases (FOG) using catalytic transesterification with methanol. These fuels have poor cold‐flow properties depending on the fatty acid (FA) composition of the parent FOG. Improving the cold‐flow properties of biodiesel will enhance its prospects for use during cooler months in moderate temperature climates. This work is a study on the use of skeletally branched‐chain alkyl esters (BCAE) composed of the isopropyl, n ‐butyl, and 2‐ethylhexyl esters of iso‐oleic acid isomers (iPr‐iOL, nBu‐iOL, and 2EH‐iOL). These BCAE additives were tested in blends with linear‐FAME (L‐FAME) derived from soybean oil (SME), lard (LME), tallow (TME), and sewage scum grease (SGME). Binary L‐FAME/SME admixtures were also studied. Admixtures were tested for the effects of the additives on cloud point (CP), pour point (PP), and kinematic viscosities at standard ( ν 40 = 40 °C) and low temperatures ( T L ) =  CP  + 5 °C ( ν L ). Although the BCAE additives were more effective than SME, relatively large additive concentrations ( y Add ) were needed to depress CP and PP by more than 2 °C. Admixtures with high concentrations of BCAE additive had ν 40  > 6.0 mm 2 s −1, the maximum limit in ASTM fuel specification D 6751. While the iPr‐iOL and nBu‐iOL additives may be blended at concentrations up to yAdd  = 0.50, 2EH‐iOL should not exceed y Add  = 0.28 in LME, 0.31 in SGME, 0.35 in TME, or 0.41 in SME to avoid driving the admixture out of specification. Some anomalies observed in the results at low y Add for SGME/BCAE admixtures were speculated to have been affected by the low‐temperature rheology of SGME.